1985
DOI: 10.1002/j.1460-2075.1985.tb04124.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding and bending of the lambda replication origin by the phage O protein.

Abstract: We have characterized the binding of lambda phage replication initiation protein O to the phage origin of replication. The minimal DNA segment required for O binding is the single iteron, a 19‐bp sequence of hyphenated dyad symmetry that is repeated with variations four times in the origin. The isolated amino terminus of O protein is also sufficient to bind DNA. Electrophoretic studies show that the amino terminus of O protein induces bending of a single iteron. The DNA‐protein interaction was characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 38 publications
3
44
0
Order By: Relevance
“…Although increased DNA flexibility might be expected to aid longdistance enhancer-promoter interactions, it is also possible that by facilitating the appropriate protein-protein interactions, increased flexibility could assist formation of a structure that antagonizes enhancer-promoter interactions. Increased flexibility could assist structure formation by bringing DNAbound proteins and sites on DNA into contact with each other, similar to the way DNA bends aid initiation of DNA replication (21,24,38), site-specific recombination (12,28), and transcription activation (reviewed in reference 35). Increased DNA flexibility could also help SUHW interact and interfere with factors that assist long-distance enhancer-promoter interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Although increased DNA flexibility might be expected to aid longdistance enhancer-promoter interactions, it is also possible that by facilitating the appropriate protein-protein interactions, increased flexibility could assist formation of a structure that antagonizes enhancer-promoter interactions. Increased flexibility could assist structure formation by bringing DNAbound proteins and sites on DNA into contact with each other, similar to the way DNA bends aid initiation of DNA replication (21,24,38), site-specific recombination (12,28), and transcription activation (reviewed in reference 35). Increased DNA flexibility could also help SUHW interact and interfere with factors that assist long-distance enhancer-promoter interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Deletions of one or more A tracts alter the degree of net bending. Furthermore, binding of the lambda 0 protein to lambda origin sites containing a central A tract increases the bending of the DNA (27). Ryder et al (17) found that intrinsic bending is a prerequisite for the binding of SV40 T antigen to a high-affinity site outside of the core origin.…”
Section: C T T a T C S A S T C T C C C G C T C C S C C S S A S C C mentioning
confidence: 99%
“…The locally curved DNA possibly is a sequencedependent feature recognized by some proteins (2,3,4). Proteins that induce or stabilize bends in specific DNA sequences are involved in a variety of cellular processes including site-specific recombination (5), DNA replication (6,7,8), chromatin organization (1) and gene regulation (9). Since the electrophoretic mobility of DNA fragments gels is dependent on their average shape, a curved DNA molecule migrates at a different rate than a linear fragment with the same number of base pairs; bent protein-DNA complexes behave in a analogous manner.…”
Section: Introductionmentioning
confidence: 99%